ANALYSIS OF CRITICAL DISCOURSE STUDY TEUN A.VAN DIJK ON THE EDITORIAL OF MEDIA INDONESIA REGARDING PERPU NO. 2/2022 - Iman Abdurohman; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe the critical discourse analysis of the editorial of Media Indonesia on January 3, 2,023 with the theme "Executive Defiance". The reason for choosing this theme is because this problem has attracted public attention to the government's defiance of the Constitutional Court's decision which stated Law No. 11 of 2020 concerning the Omnibus Law was declared conditionally unconstitutional, so the government had to revise it within 2 years. However, the government instead issued Perpu No. 2 of 2022. This has drawn criticism from various parties. This study aims to describe how the macrostructure, superstructure, and social cognition of Media Indonesia editorials with the title "executive defiance". The theory used is the Teun A Van Djik model with the documentation method and note-taking. After analysis, it was concluded that an editorial by Media Indonesia with the title "executive defiance" met the macro-structural requirements, namely: statement of opinion, argumentation, and affirmation. The straightforward superstructure of language uses declarative sentences in the form of statements and arguments. For social cognition, Media Indonesia is positioned as an opposition that sides with workers. Key words: Teun A. Van Djik, editorial, Perpu No.2/2022.